Hemophagocytosis in a case with Crimean-Congo hemorrhagic fever and an overview of possible pathogenesis with current evidence - Bıçakçı, Zafer; Tavil, Betül; Tezer, Hasan; Olcay, Lale (The Turkish Journal of Pediatrics, 2013)
Hemophagocytic lymphohistiocytosis (HLH) is a clinicopathologic condition characterized by high fever, hepatosplenomegaly, cytopenia, hyperferritinemia, and increased hemophagocytic macrophage proliferation and activation in the reticuloendothelial system. Primary HLH is familial and is a fatal disease that begins during early childhood. Secondary HLH may be acquired after intense activation of the immune system due to infection. Clinical and biologic symptoms result from cytokines secreted by T-lymphocytes and macrophages. Subtypes of primary HLH are caused by genetic defects in several cell types, including perforin-dependent cytotoxic T-lymphocytes and natural killer (NK) cells. Secondary HLH is often associated with intracellular pathogen infections. Crimean-Congo hemorrhagic fever (CCHF) is caused by a tick-borne virus, Nairovirus, from the Bunyaviridae family. It is characterized by a poor prognosis and has a high mortality. We report the case of a 14-year-old boy living in a CCHF-endemic area with no history of tick exposure. He presented with fever, and laboratory tests showed bicytopenia and hemophagocytosis in the bone marrow aspiration. Blood samples were polymerase chain reaction (PCR)-negative for CCFH but immunoglobulin (Ig)M-positive. In conclusion, patients with hemophagocytosis should be assessed for CCHF during the evaluation of cytopenia.